The Relationship between Inter-Role Conflict and Turnover Intention in the Hospitality Industry in China: The Mediating Effect of Job Burnout - Li, Jinfei (2020)
This study aims to examine the relationship between inter-role conflict and turnover intention of individuals in the hospitality industry in China. The paper will further develop a mediation model in which inter-role conflict and its two dimensions: work-family conflict (WFC) and family-work conflict (FWC) affects turnover intention through job burnout.